2021
DOI: 10.1055/s-0041-1729912
|View full text |Cite
|
Sign up to set email alerts
|

A High-Echoic Layer Surrounding the Heart Suggesting Cardiac Tamponade by Clotting

Abstract: A 16-year-old boy experienced a sudden loss of consciousness. On arrival, he was in cardiac arrest. An ultrasound study revealed a high-echoic layer surrounding the heart. He received a diagnosis of clotting cardiac tamponade. Urgent thoracotomy with pericardiotomy was performed, but he failed to obtain return of spontaneous circulation. Physicians should focus on not only low-echoic but also high-echoic areas to accurately diagnose clotting, which can result in a critical condition if not managed properly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We attempted key methods to promptly identify patients experiencing cardiac arrest due to cardiac tamponade, aiming for the immediate relief of the tamponade. This was necessary as ultrasound frequently proved ineffective in detecting tamponade caused by coagulation, if there is a lack of careful observation or if physicians are inexperienced [ 1 , 3 ]. If the presence of cardiac tamponade can be clarified, even in cases of cardiac arrest, decompression can be performed in expectation of ROSC, and the number of patients able to return to society can be improved [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted key methods to promptly identify patients experiencing cardiac arrest due to cardiac tamponade, aiming for the immediate relief of the tamponade. This was necessary as ultrasound frequently proved ineffective in detecting tamponade caused by coagulation, if there is a lack of careful observation or if physicians are inexperienced [ 1 , 3 ]. If the presence of cardiac tamponade can be clarified, even in cases of cardiac arrest, decompression can be performed in expectation of ROSC, and the number of patients able to return to society can be improved [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of cardiac arrest, we routinely investigate the cause by ultrasonography, and unless the patient is known to have terminal cancer or the family does not wish for it, blood tests and computed tomography (CT) are performed [1][2][3][4][5]. The causes of cardiac arrest include thoracic aortic diseases, some of which can lead to cardiac arrest via cardiac tamponade.…”
Section: Introductionmentioning
confidence: 99%
“…Tomita and colleagues [16] reported that such social support adds vitality to patients and reduces daily burdens. A previous study showed that many Japanese people consider that receiving support from others is a nuisance and feel apologetic about it [35] . Therefore, Japanese patients with ulcerative colitis may be reluctant to discuss their problems with others even if they are having trouble.…”
Section: Discussionmentioning
confidence: 99%